Dry matter production mean, dry matter production coefficient of variation, proportion of dry matter from crops - Fraval, Simon; Mutua, John Y.; Notenbaert, An Maria Omer; Thornton, Philip K.; Duncan, Alan J. (International Center for Tropical Agriculture, 2020)
The Techfit tool provides a means to identify suitable feed technologies to address four key constraints: dry season feed availability, growing season feed availability, feed quantity and feed quality. It is difficult to monitor animal feed availability and quality directly, this is because biomass is not necessarily utilized on the day of growth and deficits can be supplemented with imports from other locations. Instead of monitoring feed availability and quality directly, we estimate proxies, including: length of cropping period (LCP), total annual animal feed production, coefficient of variation of feed production and the proportion of crop residues. Remotely sensed and other spatially representative data provide a basis for generating these proxies.